2001
DOI: 10.1136/qhc.0100061
|View full text |Cite
|
Sign up to set email alerts
|

Preferences and understanding their effects on health

Abstract: Preference for a particular intervention may, possibly via complicated pathways, itself confer an outcome advantage which will be subsumed in unblind randomised trials as part of the measured eVectiveness of the intervention. Where more attractive interventions are compared with less attractive ones, any diVerence could therefore be a consequence of attractiveness and not its intrinsic worth. For health promotion interventions this is clearly important, but we cannot tell how important it is for therapeutic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Allowing people to choose the type of health related intervention that most appeals to them is an attractive idea, and has been thought to improve adherence and outcomes [6]. Process data from the study, reported elsewhere [5], indicated that, after controlling for the effects of sociodemographic variables, participants who chose and got a group format were over four times more likely to attend at least one class and were almost twice as likely to have a higher level of attendance as the women randomized to the group format.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allowing people to choose the type of health related intervention that most appeals to them is an attractive idea, and has been thought to improve adherence and outcomes [6]. Process data from the study, reported elsewhere [5], indicated that, after controlling for the effects of sociodemographic variables, participants who chose and got a group format were over four times more likely to attend at least one class and were almost twice as likely to have a higher level of attendance as the women randomized to the group format.…”
Section: Discussionmentioning
confidence: 99%
“…Choosing the intervention most amenable to an individual situation may enhance motivation and, therefore, program efficacy. Further, often such interventions address psychological factors such as confidence to change behavior or the belief that taking an action will produce the desired outcome and various learning events attempt to elicit these responses [6]. The extent to which a patient prefers the pedagogical means by which this new learning is expected to occur may influence results [7].…”
Section: Introductionmentioning
confidence: 99%
“…Patients' attitudes toward treatment not only affect choice but also adherence [3][4][5], individuals being very utilitarian concerning treatments, 'choosing therapies and providers which help them without regard to type, ideology or theoretical construct' [6]. In addition, treatment appraisal also has been found to affect outcome [7], possibly through psychological mechanisms similar to the placebo effect [8], although the extent of this influence is limited [9,10]. Complementary and alternative medicine (CAM) provides a good example of the influence of treatment attractiveness and experience on treatment choice and adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Accounting for treatment preferences is appealing to persons who would have refused enrollment for fear of receiving the non-preferred treatment. This strategy is believed to overcome the barrier to enrollment (related to preferences) in a RCT, thereby increasing participation rate and enhancing sample representativeness of all subgroups comprising the target population (McPherson & Britton, 2001). The limited available empirical evidence is inconclusive in supporting this claim.…”
Section: Enrollment Pattern In Prctmentioning
confidence: 99%
“…Eligible persons may decline enrollment in a RCT because of strong preferences for the treatment options under evaluation. They are not willing to take the risk of being randomly assigned to the least preferred option (McPherson & Britton, 2001;TenHave, Coyne, Salzer & Katz, 2003). Low enrollment rate of persons with strong preferences results in a sample size which is smaller than required to attain adequate statistical power.…”
mentioning
confidence: 99%